ESBL-Producing Enterobacteriaceae Isolated from Hospital and Community Health Center Wastewater in Pekanbaru, Indonesia - Muhamad Afham; Dewi Anggraini; Adrianison Adrianison; Rosantia Sarassari; Sundari Sundari (Majalah Kedokteran Bandung, 2026)
Wastewater originating from medical facilities, particularly hospitals, serves as an important reservoir for Extended-Spectrum Beta-Lactamase (ESBL)-producing bacteria. This study assessed ESBL-producing strains of Escherichia coli and Klebsiella pneumonia in the inlet and outlet of wastewater treatment systems, as well as in downstream sewage from a community health center and a public provincial referral hospital in Pekanbaru, Indonesia, during the period of Oktober to December 2023. The analysis included the enumeration of bacterial colonies for presumptive ESBL-producing E. coli and K. pneumoniae, phenotypic confirmation of ESBL production, and identification of ESBL-associated genes. Substantial quantities of presumptive ESBL-producing E. coli and K. pneumoniae were identified in both the inlet and outlet of hospital wastewater, as well as in downstream sewage water. In contrast, wastewater from the community health center contained only E. coli in the inlet samples. Phenotypic testing confirmed ESBL production in two samples (11.1%). The ESBL genes blaCTX, blaTEM, and blaSHV were detected in seven (38.9%), three (16.7%), and one isolates (11.1%), respectively. These findings highlight wastewater as a significant reservoir of ESBL-producing bacteria and underscore the need for strengthened strategies to limit their release into the environment. Effective mitigation requires targeted measures to reduce ESBL-producing bacteria in wastewater, along with continuous monitoring and control of wastewater treatment systems to prevent further dissemination of antibiotic resistance into aquatic ecosystems.